Methods of isolation and purification of outer membrane vesicles from gram-negative bacteria - Klimentová, Jana; Stulík, Jiří (Microbiological research, 2015)
Outer membrane vesicles secreted by gram-negative bacteria play an important role in bacterial physiology as well as in virulence and host-pathogen interaction. Isolated vesicles of some bacteria have also been studied for their immunomodulatory potential in the vaccine development. However, the production of vesicles in sufficient amount, purity and reproducibility remains a critical challenge for subsequent analyses in most bacteria. In the present review methods of production, isolation, purification and quantification of outer membrane vesicles are summarized and discussed.
Keywords: Subcellular Fractions; fyziologický stres; genetické inženýrství; Stress, Physiological; Secretory Vesicles; Genetic Engineering; Gram-Negative Bacteria; gramnegativní bakterie; frakcionace buněk; buněčná stěna; Cell Wall; sekreční vezikuly; Cell Fractionation; subcelulární frakce